The Hepatitis C virus NS5A and core proteins exert antagonistic effects on HAMP gene expression: the hidden interplay with the MTF‐1/MRE pathway. Issue 1 (13th December 2020) - Dimitriadis, Alexios; Foka, Pelagia; Kyratzopoulou, Eleni; Karamichali, Eirini; Petroulia, Stavroula; Tsitoura, Panagiota; Kakkanas, Athanasios; Eliadis, Petros; Georgopoulou, Urania; Mamalaki, Avgi
Abstract : Hepcidin, a 25‐amino acid peptide encoded by the HAMP gene and produced mainly by hepatocytes and macrophages, is a mediator of innate immunity and the central iron‐regulatory hormone. Circulating hepcidin controls iron efflux by inducing degradation of the cellular iron exporter ferroportin. HCV infection is associated with hepatic iron overload and elevated serum iron, which correlate with poor antiviral responses. The HCV nonstructural NS5A protein is known to function in multiple aspects of the HCV life cycle, probably exerting its activity in concert with cellular factor(s). In this study, we attempted to delineate the effect of HCV NS5A on HAMP gene expression. We observed that transient transfection of hepatoma cell lines with HCV NS5A resulted in down‐regulation of HAMP promoter activity. A similar effect was evident after transduction of Huh7 cells with a recombinant baculovirus vector expressing NS5A protein. We proceeded to construct an NS5A‐expressing stable cell line, which also exhibited down‐regulation of HAMP gene promoter activity and significant reduction of HAMP mRNA and hepcidin protein levels. Concurrent expression of HCV core protein, a well‐characterized hepcidin inducer, revealed antagonism between those two proteins for hepcidin regulation. In attempting to identify the pathways involved in NS5A‐driven reduction of hepcidin levels, we ruled out any NS5A‐induced alterations in the expression of the well‐known hepcidin inducers SMAD4 and STAT3. Further analysis linked the abundance of intracellular zinc ions and the deregulation of the MTF‐1/MRE/hepcidin axis with the observed phenomenon. This effect could be associated with distinct phases in HCV life cycle. Abstract : During HCV infection, the multifunctional core and NS5A viral proteins regulate the iron‐regulatory hormone hepcidin expression antagonistically. While hepcidin is enhanced by core‐mediated activation of BMP/SMAD and STAT3 pathways, it is down‐regulated by NS5A independently of these factors. Herein, we show that NS5A disturbs the MTF‐1/Zn 2+ /hepcidin positive regulation axis, by mopping up Zn 2+, thereby preserving the structural integrity of NS5A dimers.